The Role of Pilot Studies in Financial Regulation - Harris, Larry; Kahn, Charles; McDonald, Robert; Spatt, Chester (The Review of Corporate Finance Studies, 2025)
Abstract Financial regulators considering the desirability of a new rule or regulation sometimes use pilot studies for evidence-based decision making. Although pilot studies can generate new knowledge, they also can be expensive and subject to serious selection biases, spillover problems, and the infeasibility of a blind design. Alternatively, regulators can often evaluate a proposed regulation’s impact by analyzing archival data or applying theory based on well-accepted economic principles. We discuss why pilot studies can be useful, but also why regulators and industry participants sometimes favor pilot studies with little scientific value. We illustrate these issues by discussing various SEC pilot studies. (JEL G18, G28, G38, K22, L51)